Front Cover: The Discovery of LML134, a Histamine H3 Receptor Inverse Agonist for the Clinical Treatment of Excessive Sleep Disorders (ChemMedChem 13/2019). (3rd July 2019) - Troxler, Thomas; Feuerbach, Dominik; Zhang, Xuechun; Yang, Charles R.; Lagu, Bharat; Perrone, Mark; Wang, Tie‐Lin; Briner, Karin; Bock, Mark G.; Auberson, Yves P.
Abstract : The Front Cover shows the therapeutic effect of the H3 receptor inverse agonist LML134 (18b ), as expected in narcoleptic patients. Compound18b results from an extensive optimization of safety and pharmacokinetic properties of several chemical series. It was selected for its ability to achieve high receptor occupancy in the brain within a short time frame, followed by fast target disengagement. This profile was designed to increase wakefulness during the day and help re‐establish a normal sleep pattern, without the risk of mechanism‐related insomnia during the night following drug administration. Compound18b completed Phase I studies, and is undergoing further clinical trials to confirm its wakefulness‐promoting effect in patients suffering from shift‐work disorder. More information can be found in the Full Paper by Yves P. Auberson et al. onpage 1238 in Issue 13, 2019 (DOI:10.1002/cmdc.201900176 ).